2022
DOI: 10.1039/d2ta01212j
|View full text |Cite
|
Sign up to set email alerts
|

Solar-assisted urea oxidation at silicon photoanodes promoted by an amorphous and optically adaptive Ni–Mo–O catalytic layer

Abstract: Enabling Si to perform solar photoelectrocatalysis is a tedious task due to its low stability and because it requires interfacial catalytic layers that can impede light absorption. Here, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…In this frame, hydrothermal deposition may be useful. 65 Structured surfaces possess high surface defects which often affect the overall efficiency of Si photoelectrodes. Hence, the study of wet defect passivation strategies compatible with operation in aqueous media could be beneficial for increasing the photoelectrode performance.…”
Section: Conclusion and Overview Of Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this frame, hydrothermal deposition may be useful. 65 Structured surfaces possess high surface defects which often affect the overall efficiency of Si photoelectrodes. Hence, the study of wet defect passivation strategies compatible with operation in aqueous media could be beneficial for increasing the photoelectrode performance.…”
Section: Conclusion and Overview Of Future Developmentsmentioning
confidence: 99%
“…For that reason, the focus should be placed on alternative strategies allowing the use of thicker and denser coatings. In this frame, hydrothermal deposition may be useful . Structured surfaces possess high surface defects which often affect the overall efficiency of Si photoelectrodes.…”
Section: Conclusion and Overview Of Future Developmentsmentioning
confidence: 99%
“…To demonstrate this, highly active and stable n-Si/SiO x /Ni/NiMoO x photoanodes were developed by Loget and co-workers The n-type Si was sequentially covered with Ni and amorphous NiÀ MoÀ O films. [50] In the absence of urea, the outside-generated NiOOH species brought about a considerable decrease in transmittance to the Si substrate, especially when converting NiMoO x to an absorbing layer in the visible light region. Thus, the opaque NiOOHrich catalytic film decreased the limiting photocurrent density.…”
Section: Photoelectrochemical Systemsmentioning
confidence: 99%
“…Considering the thick catalyst layer outside, its optical properties could lead to a decrease in photon flux reaching the photoanode substrate (e. g., PEC‐OER anode), greatly restricting the solar efficacy and photocurrent density. To demonstrate this, highly active and stable n‐Si/SiO x /Ni/NiMoO x photoanodes were developed by Loget and co‐workers The n‐type Si was sequentially covered with Ni and amorphous Ni−Mo−O films [50] . In the absence of urea, the outside‐generated NiOOH species brought about a considerable decrease in transmittance to the Si substrate, especially when converting NiMoO x to an absorbing layer in the visible light region.…”
Section: Photo‐driven Urea Conversion Systemsmentioning
confidence: 99%
“…Nickel-based catalysts, as the most widely studied electrocatalysts, possess the superiorities of low onset potential to 1.5 V versus reversible hydrogen electrode (RHE), high current density and stability for electrochemical UOR (EC-UOR). [3,5,[14][15][16][17][18][19][20][21][22][23][24][25] Therefore, it has been widely combined as cocatalysts for PEC-UOR. For example, Li et al reported the PEC-UOR process from urine to hydrogen production by using Ni(OH) 2 modified TiO 2 photoanode for the first time.…”
Section: Introductionmentioning
confidence: 99%